Negative feedback in NO/cGMP signalling. (26th October 2005) - Koesling, D.; Mullershausen, F.; Lange, A.; Friebe, A.; Mergia, E.; Wagner, C.; Russwurm, M.
Abstract : Most of the effects of the signalling molecule nitric oxide (NO) are mediated by the stimulation of the NO-sensitive GC (guanylate cyclase) and the subsequent increase in cGMP formation. The enzyme contains a prosthetic haem group, which mediates NO stimulation. In addition to the physiological activator NO, NO-sensitizers like the substance YC-1 sensitize the enzyme towards NO and may therefore have important pharmacological implications. Two isoforms of NO-sensitive GC have been identified to date that share regulatory properties, but differ in the subcellular localization. The more ubiquitously expressed α1 β1 heterodimer and the α2 β1 isoform are mainly expressed in brain. In intact cells, NO-induced cGMP signalling not only depends on cGMP formation, but is also critically determined by the activity of the enzymes responsible for cGMP degradation, e.g. PDE5 (phosphodiesterase 5). Recently, direct activation of PDE5 by cGMP was demonstrated, limiting the cGMP increase and thus functioning as a negative feedback. As the cGMP-induced PDE5 activation turned out to be sustained, in the range of hours, it is probably responsible for the NO-induced desensitization observed within NO/cGMP signalling.